MONITORING OF CLINICAL EFFICIENCY INDICATORS DIFFERENTIATED APPROACH TO THE CHOICE OF TACTICS OF PROFESSIONAL HYGIENE - Nazaryan, R.S.; Krivenko, L.S. (World of Medicine and Biology, 2013)
The aim was to study the change in clinical indicators of different algorithms of professional hygiene. 62 patients were examined, all held professional hygiene. As a result it was identified the improvements by the addition of stage of finishing restorations and better clinical efficacy of air-abrasive polishing system.
Keywords: professional hygiene; hygienic status; caries intensity; tooth sensitivity